2015
DOI: 10.1007/s12649-015-9392-1
|View full text |Cite
|
Sign up to set email alerts
|

An Artificial Neural Network and Genetic Algorithm Optimized Model for Biogas Production from Co-digestion of Seed Cake of Karanja and Cattle Dung

Abstract: In this study, experiments were conducted with four different proportions of seed cake of Karanja (SCK) and cattle dung (CD) mixture, for biogas production. 75, 50 and 25 % of the SCK on a mass basis were mixed with 25, 50 and 75 % of the CD and, named as S 1 , S 2 and S 3 . For comparison, biogas obtained from 100 % CD (S 4 ) was considered. The samples were kept in four different reactors, for 30 days of observation, and the yield of biogas from the samples S 1 , S 2 and S 3 was evaluated. Modeling was carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(11 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…One direct effect of grazing is through production of dung and urine McNaughton et al, 1997). Our study showed that the relative abundance of Bacteroidia, an obligate anaerobic gut microbe in animals (Eckburg, 2005;Winter & Bäumler, 2014), was higher in WG, likely due to accumulation of dung and urine by intensive grazing in WG (Barik & Murugan, 2015). Accumulation of dung and urine may also decrease the C/N of substrates, facilitating decomposition but reducing soil C accumulation (Bagchi, Roy, Maitra, & Sran, 2017;Fontaine et al, 2011).…”
Section: Direct Impacts Of Grazing On Microbes Through Altering Soimentioning
confidence: 71%
“…One direct effect of grazing is through production of dung and urine McNaughton et al, 1997). Our study showed that the relative abundance of Bacteroidia, an obligate anaerobic gut microbe in animals (Eckburg, 2005;Winter & Bäumler, 2014), was higher in WG, likely due to accumulation of dung and urine by intensive grazing in WG (Barik & Murugan, 2015). Accumulation of dung and urine may also decrease the C/N of substrates, facilitating decomposition but reducing soil C accumulation (Bagchi, Roy, Maitra, & Sran, 2017;Fontaine et al, 2011).…”
Section: Direct Impacts Of Grazing On Microbes Through Altering Soimentioning
confidence: 71%
“…Correspondingly, the biogas from the sample had a heating value of 27.5 MJ/kg, with an energy content of 6–6.5 kW/m 3 . Barik and Murugan (2015) further studied modeling of the process for prediction and optimisation of biogas production using artificial neural network (ANN) and the genetic algorithm (GA) [ 93 ]. The GA optimised results based upon ANN developed model for pH, digestion time and the C/N ratio of the samples were correlated with the experimental results.…”
Section: Biogas Productions From Non-edible Oil Cakesmentioning
confidence: 99%
“…Dibaba et al [87] determined that the best performance of Upflow Anaerobic Contactor (UAC) with 87% COD removal, and hydraulic retention time of 16.67 days where an increase of 7.4% in biogas production was realized. Barik and Murugan [88] used ANN and GA to estimate and optimize the yield of biogas from cattle dung and seed cake of Karanja in co-digestion. The product quality using co-digestion of cake of Karanja and cattle dung mixture was higher than when using cattle dung samples for a mixing ratio of 1 cake of Karanja to 3 cattle dung.…”
Section: Optimization Of Quality and Yieldmentioning
confidence: 99%